Penyelesaian Sengketa Tanah Dengan Hak Guna Usaha dalam Penertiban Tanah Terlantar - Vera Siti Parihah (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2022)
Abstract: Land is a gift that comes from God Almighty. Soil plays an important role for society and plants. one of which is realized by granting land rights to citizens for land farmers who play an important role in depending on their lives from crops. Land rights that have developed quite rapidly are Cultivation Rights. The usufructuary right is contained in Law Number 5 of 1960 UUPA in Article 28 Paragraph 1 it is stated that the usufructuary right is the right to cultivate land controlled by the state for a certain period of time for agriculture, fishery and animal husbandry businesses. The research aims to find the right solutions for various land use conflicts, especially in optimizing the use of abandoned land. This solution is needed to avoid potential horizontal conflicts between communities, companies and the government since 1993. Abandoned land is a termination of legal relations between subjects and objects over land then the land was re-occupied by the state. The problem of controlling abandoned land is increasingly complex with the many interests of various parties in land. This also raises several problems with the land used in the business world. Such as disputes over the management of abandoned land and farming rights, owned by a plantation company, namely PT. Agrosari Merapi in West Pasaman Province against the Regent of West Pasaman Regency. This controversy arose from West Pasaman district No. 525/1898/BUP-PASBAR regarding the closure of PT. Agrosari Merapi, West Passaman Regency, October 3, 2011. The decision of the Regent of West Pasaman was based on the following demands that PT. Agrosari Merapi relinquished land rights to cultivate a land area of 3,160 ha. Based on the results of the research, it can be argued that the Dispute Settlement Process for Abandoned Land against Cultivation Rights was resolved through the Padang State Administrative Court in accordance with Law Number 5 of 1986 concerning Administrative Courts. Keywords: dispute resolution, land, usufructuary rights, control, abandoned land Abstrak: Tanah merupakan karunia yang datang dari Tuhan Maha Esa. Tanah berperan penting untuk masyarakat maupun tumbuhan. salah satunya diwujudkan dengan pemberian hak atas tanah kepada warga negara bagi petani tanah berperan penitng untuk menggantungkan hidupnya dari hasil panen. Hak atas tanah yang mengalami perkembangan yang cukup pesat adalah Hak Guna Usaha. Hak guna usaha tercantum pada UU Nomor 5 Tahun 1960 UUPA dalam Pasal 28 Ayat 1 disebutkan, hak guna usaha adalah hak untuk mengusahakan tanah yang dikuasai oleh negara dalam jangka waktu tertentu untuk usaha pertanian, perikanan, dan peternakan. Penelitian bertujuan untuk mencari solusi yang tepat atas berbagai konflik penggunaan lahan, khususnya dalam mengoptimalkan pemanfaatan lahan terlantar solusi ini diperlukan untuk menghindari potensi konflik horizontal antara masyarakat, perusahaan dan pemerintah sejak tahun 1993. Tanah terlantar merupakan pemutusan hubungan hukum antar subjek dengan objek atas tanah kemudian tanah tersebut dikuasai kembali oleh negara. Permasalahan penertiban tanah terlantar semakin kompleks dengan banyaknya kepentingan berbagai pihak atas tanah. Hal ini juga menimbulkan beberapa permasalahan terhadap tanah yang digunakan dalam dunia usaha. Seperti sengketa pengelolaan lahan terlantar dan hak bertani, dimiliki oleh perusahaan perkebunan yaitu PT. Agrosari Merapi di Provinsi Pasaman Barat melawan Bupati Kabupaten Pasaman Barat. Kontroversi ini muncul dari kabupaten Pasaman Barat No. 525/1898/BUP-PASBAR terkait penutupan PT.Agrosari Merapi, Kabupaten Passaman Barat, 3 Oktober 2011. Keputusan Bupati Pasaman Barat didasarkan pada tuntutan sebagai berikut PT.Agrosari Merapi melepaskan hak atas tanah untuk mengolah tanah seluas 3.160 ha. Berdasarkan hasil penelitian dapat dikemukakan bahwa Proses Penyelesaian Sengketa Penertiban Tanah terlantar terhadap Hak Guna Usaha diselesaikan melalui Pengadilan Tata Usaha Negara Padang sesuai dengan UU Nomor 5 Tahun 1986 tentang PTUN.Kata Kunci: Penyelesaian sengketa, Tanah, Hak guna Usaha, Penertiban, tanah terlantar